The role of fenugreek (Trigonella foenum-graecum), sesame (sesamum indicum), and domperidone in detecting the mammary glands of lactating white rats - Israa Hashim Ali; Munif Saob Ahmed; Aziz Khalid Hamid (Tikrit Journal of Pure Science, 2021)
This study was designed to impact the effect of fenugreek (Trigonella foenum-graecum), sesame (sesamum indicum), and domperidone on the mammary glands of pregnant white rats spices Rattus norvegicus at different concentrations. Fenugreek was used in an oral dose of 0.5 ml / day as oil, while sesame was used with a dose of 1 g / day as powder and domperidone was used as liquid as an oral dose of 2 mg / day .